Schrodinger : Life and Thought - Moore, Walter J. (New York : CUP, 1989)
This is a biography of the great scientist, Erwin Schroedinger (author of "What is Life?"), which draws upon recollections of his family and friends, as well as on contemporary records, diaries and letters. It aims to reveal the fundamental motives that drove him.
Includes References 483-501p.; Index 502-513p.
Keywords: Biography; Physics; Schrodinger-life and thought; General Science